Synthesis, Characterization, and Control Release of Zinc Layered Nitrate Intercalated with Beta-Napthoxyacetic Acid (BNOA) Nanocomposite - Abd Rahim, Hasnatul Fitriah; Jalil, Mohammad Nor; Sarijo, Siti Halimah; Buyong, Faeiza; Zaki, Hamizah Mohd (Universitas Gadjah Mada, 2024)
In this research, the synthesis of the host using zinc nitrate-hexahydrate as a precursor to form zinc layered nitrate (ZLN) and the guest anion which is beta-napthoxyacetic acid (BNOA) will be intercalated with the ZLN to produce nanocomposites called ZLN/beta-napthoxyacetic acid (ZLNB). The method used for the synthesis of the host was self-assembly and ion exchange. The nanocomposites were confirmed with the basal spacing increases from 9.8 to 28.2 Å by using powder X-ray diffraction (PXRD). Therefore, proved the bigger basal spacing compared to the layered double hydroxide of MgAl and ZnAl. The appearance of the FTIR shift band at 1603 cm−1 of C=C aromatic ring indicates that the anions have been successfully incorporated into the interlayers of ZLNB. Moreover, the loading percentage estimated by the carbon content from the ZLNB determined by CHNS analyzer was 41.8% (w/w). The morphology analysis confirmed the plate-like structure for ZLN into flaky-like with irregular, porous and unambiguous structure for ZLNB by field emission scanning electron microscopy (FESEM). The controlled release property showed that the release of BNOA in the various aqueous solutions is in the order of Na3PO4 > Na2SO4 > NaCl and fitted into pseudo-second-order kinetic models.